solve x+3/x-3+x+2/x-2=2
Answers
Answered by
77
First take the LCM of above expression
we get
( x +3)(x-2) + (x+2)(x-3)/ (x-3)(x-2) =2
expand it
x ^2 +3x - 2x -6+ x^2 +2x -3x -6= 2 ( x-3)(x-2)
2x^2 -12 = 2(x^2 -3x - 2x +6)
2x^2 -12 = 2x^2 -10x +12
10x = 24
x = 12/5 is your answer
when you put it in expression
you get -9 + 11= 2
Hope it helps
we get
( x +3)(x-2) + (x+2)(x-3)/ (x-3)(x-2) =2
expand it
x ^2 +3x - 2x -6+ x^2 +2x -3x -6= 2 ( x-3)(x-2)
2x^2 -12 = 2(x^2 -3x - 2x +6)
2x^2 -12 = 2x^2 -10x +12
10x = 24
x = 12/5 is your answer
when you put it in expression
you get -9 + 11= 2
Hope it helps
Answered by
38
HOPE IT IS USEFUL FOR YOU
PLZ MARK AS BRAINLIST
PLZ MARK AS BRAINLIST
Attachments:
![](https://hi-static.z-dn.net/files/db1/4cabe84e27c721ffc20d7c0f89791153.jpg)
ayushpat1999:
when you put 3 in denominator you get 0 and denominator in 0 is not defined
Similar questions
Science,
8 months ago
Math,
8 months ago
Accountancy,
8 months ago
Social Sciences,
1 year ago
Math,
1 year ago
Computer Science,
1 year ago